UV-Enhanced removal of enrofloxacin in water using oyster shell-derived CaO-ZnO composite - Sihombing Mastavioni; Azizah Nurfiah; Febriyanti Siti; Miraza Adithya Zulfadli; Prajaputra Vicky; Isnaini Nadia; Karina Sofyatuddin; Riswan M. (BIO Web of Conferences)
The contamination of aquatic environments by enrofloxacin, a commonly used veterinary antibiotic, poses serious risks to both ecosystem health and human safety. This study investigates the potential of calcium oxide-zinc oxide (CaO-ZnO) composites derived from oyster shells for the UV-enhanced degradation of enrofloxacin in water. The CaO-ZnO composites were synthesized via calcination of oyster shells mixed with zinc oxide and characterized using X-ray diffraction (XRD) to determine their mineral properties. Enrofloxacin was detected at a maximum absorption wavelength of 272 nm using UV-Vis spectroscopy. The removal efficiency of the CaO-ZnO composites was assessed at room temperature, with varying contact times (30-150 minutes) and pH levels (3, 6, and 9). The results demonstrated that the CaO-ZnO composite achieved the best performance at pH 3, with a removal efficiency of 42.87% after 150 minutes. Under UV light from sunlight, the removal efficiency was significantly enhanced, reaching 61.04% compared to 14.53% for CaO. These findings suggest that CaO-ZnO composites derived from oyster shells are promising materials for the effective UV-enhanced removal of enrofloxacin from contaminated water sources. However, further improvements are needed by optimizing additional parameters to enhance their effectiveness.